1988
DOI: 10.1017/s0033291700002026
|View full text |Cite
|
Sign up to set email alerts
|

Development of a questionnaire measure of adjustment to cancer: the MAC scale

Abstract: SynopsisThis paper describes the development of a self-rating scale to measure adjustment to cancer. The Mental Adjustment to Cancer (MAC) Scale has been completed by 235 patients with various types and stages of cancer. It is easily understood by, and acceptable to, patients. Data relating to reliability and internal consistency indicate that the MAC scale is a valuable research tool for clinical studies of patients' psychological adjustment to cancer.

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
4
1

Citation Types

17
463
9
28

Year Published

1996
1996
2005
2005

Publication Types

Select...
8

Relationship

0
8

Authors

Journals

citations
Cited by 580 publications
(517 citation statements)
references
References 18 publications
17
463
9
28
Order By: Relevance
“…The possible responses to each statement are: (1) 'definitely does not apply to me', (2) 'does not apply to me', (3) 'applies to me' and (4) 'definitely applies to me'. Previous studies have suggested that the MAC scale has adequate validity and reliability (Watson et al, 1988Greer et al, 1989). Our previous study also disclosed that the Japanese version of the MAC scale is valid and reliable (Akechi et al, 1997).…”
Section: Methodsmentioning
confidence: 55%
See 1 more Smart Citation
“…The possible responses to each statement are: (1) 'definitely does not apply to me', (2) 'does not apply to me', (3) 'applies to me' and (4) 'definitely applies to me'. Previous studies have suggested that the MAC scale has adequate validity and reliability (Watson et al, 1988Greer et al, 1989). Our previous study also disclosed that the Japanese version of the MAC scale is valid and reliable (Akechi et al, 1997).…”
Section: Methodsmentioning
confidence: 55%
“…The MAC scale is a self-rating scale developed in the United Kingdom (Watson et al, 1988). The scale consists of five subscales: fighting spirit, anxious preoccupation, fatalism, helplessness/hopelessness and avoidance.…”
Section: Methodsmentioning
confidence: 99%
“…Although the original version of the MAC scale had only been validated in UK population (Watson et al, 1988), it has undergone assessment and validation among patient populations of other ethnicities and countries (Akechi et al, 2000;Cayrou et al, 2003;Ho et al, 2003;Mystakidou et al, 2004). In each case the internal consistency was found to be similar to that of the original version and concurrent validity and correlation was established with other frequently used tools.…”
Section: Methodsmentioning
confidence: 98%
“…Both are wellvalidated tools used to measure coping and distress in cancer patients. The MAC is a 40-item questionnaire, which incorporates five subscales to measure fighting spirit, helpless/hopelessness, anxious preoccupation, fatalism and avoidance/denial (Watson et al, 1988). Recent work suggests that the construct of denial is addressed by three questions (questions 5, 21 and 38) on the MAC scale rather than the originally proposed single item (question 38) (Nordin et al, 1999).…”
Section: Methodsmentioning
confidence: 99%
“…Cancer-Related Coping: the Mini-Mental Adjustment to Cancer Scale (short form) (MAC) 16 The MAC is a 29-item self-report questionnaire designed to assess patients' strategies for handling their cancer and is a short-form version of the original MAC, with 5 subscales: fighting spirit, helpless/hopeless, anxious preoccupation, fatalism, and cognitive avoidance. "At the moment I take one day at a time.…”
Section: 67mentioning
confidence: 99%